Mangá : do Japão ao mundo pela prática midiática do scanlation - Hirata, Tatiane (2012)
The union between vitalism of daily life and collaborative practices of ciberculture gave rise to the media practice of scanlation, an activity undertaken by fans of manga, the Japanese comics. Scanlation, contraction of words scan and translation, is the process of scanning printed mangas in order to translate them from Japanese into another language, and distributing them free of charge through internet without permission from the copyright holders. Willing to escape from capitalist subjectivity scanlation members try to subvert the traditional way of consuming manga. Gathered under the media practice of scanlation, fans around the world reinvent the process of reproduction, circulation and manga consuming in this period characterized by the process of mediatic convergence and requests for ever renewed form of rituals of sociability in urban anonymity.